Comparison of the Responses of Global Tests of Coagulation with Molecular Markers of Neutrophil, Endothelial, and Hemostatic System Perturbation in the Baboon Model of E. coli Sepsis - Wada, Hideo; Yamamuro, Miho; Inoue, Akiko; Shiku, Hiroshi; Sakuragawa, Nobuo; Redl, Heinz; Peer, Glenn; Taylor, Fletcher B., Jr. (Thrombosis and Haemostasis, 2001)
This study correlates changes in neutrophilic activity and endothelial injury with markers of hemostatic activity following the infusion of increasing concentrations of E. coli organisms. It focuses on the hemostatic response as a marker of microvascular injury and uses the response to increasing concentrations of E. coli to refine our definition of disseminated intravascular coagulation (DIC) and distinguish between a compensated (non-overt DIC) and uncompensated (overt DIC) response. We observed that the global coagulation tests reflected activation of the hemostatic system in a dose dependent manner (overt DIC) in the early phases (T+2 to 6 h) of the response to increasing concentrations of E. coli, but that they failed to do so in the late phases (T+ 24 to 48 h). We observed that molecular markers, soluble thrombomodulin and elastase, unlike thrombin/antithrombin and plasmin/antiplasmin complexes, remained elevated out to T+24 to 48 h indicating endothelial injury that persists beyond the initial inflammatory insult in compensated as well as uncompensated DIC.
Keywords: Endothelium; baboon; E. coli; hemostasis; sepsis; disseminated intravascular coagulation